More or better? Measuring quality versus quantity in food consumption - Corinna Manig; Alessio Moneta (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2009)
As people become richer they get the opportunity of consuming more but also qualitatively better goods. This holds for a basic commodity like food as well. We investigate food consumption in Russia, taking into account both expenditure and nutrition value in terms of calories. We analyze how food consumption patterns change with increasing income by estimating both 'quantity Engel curves' and 'quality Engel curves.' The former describe the functional dependence of calories consumed on total expenditure. The latter trace out the dependence of price per calorie as a proxy for quality on total expenditure. We compare income elasticities of quantity with income elasticities of quality. In these Russian data for years 2000-2002 the reaction of quality to changes in income is significantly stronger than the reaction of quantity to income changes suggesting that Russian households tend to choose higher quality food items as income rises.
Keywords: D12; 330; food consumption patterns; calorie intake; income elasticity decomposition; Engel curves; method of average derivatives; Nahrungsmittelkonsum; Mikroökonomische Konsumfunktion; Produktqualität; Einkommenselastizität; Ernährungsverhalten; Schätzung; Russland